2022
DOI: 10.1002/essoar.10512427.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquity of shallow mesoscale circulations in the trades and their influence on moisture variance

Abstract: Understanding drivers of cloud organization is crucial for accurately estimating clouds' feedback to a warming climate. Shallow mesoscale circulations are thought to play an important role in cloud organization, but they have not been observed. Here, we present observational evidence for shallow mesoscale overturning circulations (SMOCs) from divergence measurements made during the EUREC4A field campaign in the north-Atlantic trades. Meteorological reanalyses reproduce the observed lowlevel divergence well and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…In the past, there had been the concern that the large-scale vertical winds from the reanalysis winds would not be representative of the observed conditions. George et al (2022) demonstrates that the mean large-scale vertical motion observed across the EUREC 4 A-circle agrees well with the analysis, also when the sondes were not included, giving confidence in the ability of the analysis to capture the large-scale conditions.…”
Section: Eurec 4 a Observationssupporting
confidence: 70%
“…In the past, there had been the concern that the large-scale vertical winds from the reanalysis winds would not be representative of the observed conditions. George et al (2022) demonstrates that the mean large-scale vertical motion observed across the EUREC 4 A-circle agrees well with the analysis, also when the sondes were not included, giving confidence in the ability of the analysis to capture the large-scale conditions.…”
Section: Eurec 4 a Observationssupporting
confidence: 70%
“…Most of the climate models considered here simulate unrealistic cloud behaviors at the subdaily timescale. These shortcomings call for a community effort to i) analyze high-frequency model outputs to assess fast physical processes in which many uncertainties of the current climate and future projections are rooted, ii) develop parameterizations that better represent the cloud–convection coupling, the main populations of shallow cumuli observed in nature and their transition on the daily timescale, and iii) better understand the factors that influence the strength of shallow convection, including the role of shallow mesoscale circulations that are ubiquitous in the tropics and have the potential to influence trade cumulus dynamics ( 21 , 26 , 36 ). Addressing these gaps with observations that can be collected every day stands a good chance to ultimately increase the credibility of climate projections.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We investigate spatial organisation in scenes of 4 x 4 • (about 450 x 450 km), an area extent similar to previous studies (Radtke et al, 2022;George et al, 2022). Figure 1a shows three example scenes with different degrees of organisation.…”
Section: Investigating Spatial Organisation and The Pathway To Precip...mentioning
confidence: 94%
“…enhanced moisture transport into anomalously moist patches by mesoscale circulations (Narenpitak et al, 2021;George et al, 2022), larger cloud clusters that are less prone to dilution (Tian & Kuang, 2016), as well as clouds pre-conditioning the environment for subsequent convection (Kuang & Bretherton, 2006). The more favourable thermodynamic conditions allow clouds to develop under less favourable dynamic conditions, leading to a less efficient rain production.…”
Section: Bufferingmentioning
confidence: 99%